Surgery or radiotherapy for stage I lung cancer? An intention-to-treat analysis. Issue 6 (20th June 2019) - Spencer, Katie L.; Kennedy, Martyn P.T.; Lummis, Katie L.; Ellames, Deborah A.B.; Snee, Michael; Brunelli, Alessandro; Franks, Kevin; Callister, Matthew E.J.
Introduction: Surgery is the standard of care for early-stage lung cancer, with stereotactic ablative body radiotherapy (SABR) a lower morbidity alternative for patients with limited physiological reserve. Comparisons of outcomes between these treatment options are limited by competing comorbidities and differences in pre-treatment pathological information. This study aims to address these issues by assessing both overall and cancer-specific survival for presumed stage I lung cancer on an intention-to-treat basis. Methods: This retrospective intention-to-treat analysis identified all patients treated for presumed stage I lung cancer within a single large UK centre. Overall survival, cancer-specific survival, and combined cancer and treatment-related survival were assessed with adjustment for confounding variables using Cox proportional hazards and Fine–Gray competing risks analyses. Results: 468 patients (including 316 surgery and 99 SABR) were included in the study population. Compared with surgery, SABR was associated with inferior overall survival on multivariable Cox modelling (SABR HR 1.84 (95% CI 1.32–2.57)), but there was no difference in cancer-specific survival (SABR HR 1.47 (95% CI 0.80–2.69)) or combined cancer and treatment-related survival (SABR HR 1.27 (95% CI 0.74–2.17)). Combined cancer and treatment-related death was no different between SABR and surgery on Fine–Gray competing risks multivariable modelling (subdistribution hazard 1.03 (95% CI 0.59–1.81)). Non-cancer-related death was significantly higher in SABR than surgery (subdistribution hazard 2.16 (95% CI 1.41–3.32)). Conclusion: In this analysis, no difference in cancer-specific survival was observed between SABR and surgery. Further work is needed to define predictors of outcome and help inform treatment decisions. No difference seen in cancer- and treatment-specific survival following surgery and SABR. Inferior overall survival may reflect unobserved confounding. Further prospective work should assess quality of life outcomes to support shared decision making. http://ow.ly/7s5t30njP0B